2008
DOI: 10.1111/j.1742-1241.2007.01689.x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to noise in orthopaedic theatres - do we need protection?

Abstract: Noise levels in orthopaedic theatres can be at unacceptable levels, which could potentially lead to hearing problems in the staff and patients. We believe that all patients, especially the elderly patients, (who are more prone to hearing problems) should have hearing protection during orthopaedic operations that use high-powered tools. Surgeons and scrubbed theatre staff should take precautions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…surgical instruments-seem less prone to extreme noise events. Consistent with this assumption, the plethora of noise studies in the surgical context focuses on orthopaedic surgery 2,3,11 . This assumption, however, may require revision.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…surgical instruments-seem less prone to extreme noise events. Consistent with this assumption, the plethora of noise studies in the surgical context focuses on orthopaedic surgery 2,3,11 . This assumption, however, may require revision.…”
mentioning
confidence: 95%
“…Specifically, the majority of evidence-irrespective of the surgery type covered-is limited to non-processual descriptive indicators (e.g. Mean Noise Level, Standard Deviation of Noise, Maximum Noise, Minimum Noise) 2,3,15 . Processual indicators, that is, descriptive data capturing the development of noise patterns during procedures, are generally rare.…”
mentioning
confidence: 99%
“…Within healthcare settings, high environmental noise in hospitals may be responsible for abnormal hearing among healthcare workers, 3,4 while the orthopaedic staff experienced the highest prevalence of hearing-associated problems, due to highpowered tools in orthopaedic theatres. [5][6][7][8][9][10] In the 1960s, environmental noise produced in dental healthcare settings was considered responsible for HI in the dental staff. [11][12][13] However in almost all previous studies dentists did not experience higher HI risk than the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Pereira et al 3 measured noise levels during 50 trauma procedures and found that they ranged from 40 dB to 130 dB, with an average level of 85 dB. Siverdeen et al 8 found that in orthopedic procedures, several instruments create noise: saws = 95 dBA drills = 90 dBA, K‐wire drivers = 85 dBA, and hammers = 65 dBA 8 The NIOSH measured the noise levels in 18 ORs at a large, multispecialty facility and found that noise levels were the highest in the orthopedic and neurosurgery rooms, and noise levels were higher the closer a person was to the source of the sound (eg, noise levels were higher for team members working at the sterile field than for the RN circulator).…”
Section: Noise In the Ormentioning
confidence: 99%